New Advances in the Understanding of Proteases as Diagnostic and Pharmaceutical Targets in Homeostatic and Pathologic Conditions - Andrey A. Zamyatnin; Alessandro Parodi (MDPI AG, 2022)
Protease biology represents a hot topic in biomedical research because of their pivotal role in regulating cell and tissue homeostasis, regeneration and pathogenesis [...]